PENINGKATAN FOTOSTABILITAS PIGMEN BETA KAROTEN DENGAN PEMBUATAN MIKROEMULSI - Ika Agustina; Mega Efrilia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Throughout 2018, BPOM found various kinds of illegal cosmetics containing prohibited/dangerous ingredients. One of the hazardous materials found was the Red K3 textile dye on the lipstick. The solution needed is to make natural dyes that have good stability to light. The aim of this study was to increase the stability of beta carotenoid pigments to light by making microemulsions. The source of beta carotene compounds comes from Daucus carota L. The extraction technique uses maceration with ethanol:hexane (4:3) as solvent. To get the best microemulsion formulation, various concentrations of PEG 40 HCO:glycerol:extract were made. The best microemulsion formulation is code FW3 with a composition of 2:2:1 (PEG 40 HCO:glycerol:extract). Then the Daucus carota L extract and FW3 microemulsion were tested for photostability. The results of the photostability test showed a decrease in the concentration of Daucus carota L. extract by 2.84%, while the Daucus carota L microemulsion decreased by 1.33%. Both preparations are still categorized as photosensitive substances.